2016
DOI: 10.1007/s12275-017-6542-0
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus safety study for proliferation and differentiation of human adipose-derived mesenchymal stem cells

Abstract: Nucleotide and amino acid substitution pattern in vif gene of the Korean clade of HIV-1 isolated from Koreans were analyzed using consensus sequences. At nucleotide level, transition/transversion substitution ratio was 1.88, and nonsynonymous/synonymous substitution ratio was 2.67, suggesting a divergent evolution in the Korean clade. At amino acid level, there were 17 substitutions and G-->E substitution at position 37 may be responsible for change in predicted secondary structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The results showed that AD-MSCs lost their differentiation potential, followed by the loosing of a typical fibroblast-like spindle shape, leading to elevated morphological abnormality, as shown in the different conditions such as changing condition media, when infected with reovirus, while the surface markers did not change significantly. The previous report by Park and Kim 21 showed that MSCs retained their differentiation potency to adipogenic and osteogenic lineages after infection with reovirus. Other studies showed that cytomegalovirus and human immunodeficiency virus infection affected MSCs differentiation potential into osteocyte and adipocyte and also may cause changes in the surface markers of MSCs.…”
Section: Discussionmentioning
confidence: 89%
“…The results showed that AD-MSCs lost their differentiation potential, followed by the loosing of a typical fibroblast-like spindle shape, leading to elevated morphological abnormality, as shown in the different conditions such as changing condition media, when infected with reovirus, while the surface markers did not change significantly. The previous report by Park and Kim 21 showed that MSCs retained their differentiation potency to adipogenic and osteogenic lineages after infection with reovirus. Other studies showed that cytomegalovirus and human immunodeficiency virus infection affected MSCs differentiation potential into osteocyte and adipocyte and also may cause changes in the surface markers of MSCs.…”
Section: Discussionmentioning
confidence: 89%
“…The mechanism for why reovirus can infect some cancers and not others remains undefined and we speculated that an investigation into the similarities between stem cells and cancer cells provides a new avenue of investigation into what regulates this phenomenon. Although sensitivity of adult stem cells to reovirus has been investigated previously, particularly as groups are interested in using mesenchymal stem cells as carrier cells to deliver virus [ 75 , 76 ], no studies have investigated the sensitivity of pluripotent stem cells to reovirus. The first objective of this work was therefore to investigate both murine and human stem cell responses to reoviral infection.…”
Section: Resultsmentioning
confidence: 99%
“…Reovirus is capable of infecting and lysing cancer cells and cancer stem cells, and, as shown here, healthy ESCs. Intriguingly, adult (mesenchymal and hematopoietic) stem cells appear to be refractory to infection [ 76 , 86 ]. In light of the recent view that pluripotency induction shares similar pathways with carcinogenesis, it is possible to suggest that the same subset of genes that are activated in some cancers may also be up-regulated in pluripotent cells, thereby rendering them permissive to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Park and Kim investigated reoviral replication in mesenchymal stem cell populations and found that these cells were still capable of proliferation and differentiation following reoviral infection. They concluded that mesenchymal stem cell populations would be a potential carrier for reovirus to enhance systemic infections [ 51 ].…”
Section: Deliverymentioning
confidence: 99%